Transgenic Maize Methods and Protocols - Scott, M. Paul.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana Press, 2009)
As increasing global population and continuing economic development ensure the need for further production and cultivation of maize, the necessity of the application of transgenic technology to this model species and crop plant grows steadily. In Transgenic Maize: Methods and Protocols, experts in the various disciplines of the field contribute readily reproducible protocols covering such topics as transformation methods, transgenic maize in research, the analysis of transgenic plants, and breeding with transgenes. Written in the highly successful Methods in Molecular Biology$1!" (Bseries format, the chapters present brief introductions to their respective topics, lists of the necessary materials and reagents, step-by-step laboratory protocols, and notes on troubleshooting and avoiding known pitfalls. Cutting-edge and easy to use, Transgenic Maize: Methods and Protocols will greatly aid researchers wishing to use these procedures in their own laboratories, and will provide readers with a better understanding of the experiments being performed by cooperators or fee-for-service labs.s
Design of Gene Constructs for Transgenic Maize -- Transformation Methods -- Transient Expression of GFP in Immature Seed Tissues -- Biolistic Gun-Mediated Maize Genetic Transformation -- Agrobacterium-Mediated Maize Transformation: Immature Embryos Versus Callus -- Whiskers-Mediated Maize Transformation -- Transgenic Maize in Research -- Methods for Generation and Analysis of Fluorescent Protein-Tagged Maize Lines -- Use of Transgene-Induced RNAi to Regulate Endogenous Gene Expression -- Plasmid Rescue: Recovery of Flanking Genomic Sequences from Transgenic Transposon Insertion Sites -- Analysis of Transgenic Plants -- Nonradioactive Genomic DNA Blots for Detection of Low Abundant Sequences in Transgenic Maize -- Tissue-Print Immunodetection of Transgene Products in Endosperm for High-Throughput Screening of Seeds -- Determination of Transgene Copy Number by Real-Time Quantitative PCR -- Breeding with Transgenes -- Herbicide Resistance Screening Assay -- Characterizing Transgene Inheritance -- Backcross Breeding.
Keywords: Life sciences; Agriculture; Plant science; Botany; Plant genetics; Transgenic organisms; Life Sciences; Agriculture; Plant Sciences; Plant Genetics & Genomics; Transgenics; Electronic books